Predicting Academic Alienation From Emotion Dysregulation, Social Competence, and Peer Relationships in School-Attending Girls: A Multiple-Regression Approach - Vafa, Zohreh; Azizi, Morteza; Elhami Athar, Mojtaba (Frontiers in Psychology, 2021)
School Alienation (SA) refers to a collection of negative attitudes towards the social and academic realms of schooling consisting of cognitive and affective components. The current study was designed to examine whether emotion dysregulation, social competence, and peer problems predict school alienation. In this vein, 300 school-attending adolescents in Sarab were recruited and completed Difficulties in Emotion Regulation Scale (DERS), Academic Alienation Questionnaire (AAQ), Social Competence Test (SCT), and Index of Peer Relations (IPR) measures, but 280 (M age = 16.35; SD = 0.82; 46% girls) completed data were gathered. The results of hierarchical multiple regression indicated that school alienation was significantly predicted by emotion dysregulation, social competency, and peer problems. In conclusion, our findings suggest that school psychologists and other clinicians design interventions to improve the students' shortcomings in emotion regulations, social competency, and peer relationships domains.